ANALISIS PENGARUH KETERLIBATAN ORANG TUA DALAM PROSES PEMBELAJARAN ANAK DI SEKOLAH DASAR - Vina Rahmayani; Mohamad Ramdan (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Parental involvement in children's learning processes in elementary school plays a crucial role in supporting their academic success and social-emotional development. This study aims to analyze the influence of parental involvement on children's learning processes in elementary school and the forms of support that can be provided to support student learning success. The research method used was a literature study by collecting various reference sources in the form of journals, books, and previous research results relevant to the research topic. The results of the study indicate that parental involvement has a positive impact on children's learning motivation, academic achievement, communication skills, and character development. Support provided by parents can take the form of learning assistance at home, providing motivation, providing learning facilities, active communication with teachers, and attention to children's learning needs. In addition, good cooperation between schools and families can create a conducive learning environment so that children are more confident and have a high enthusiasm for learning. Conversely, a lack of parental attention and involvement can lead to low learning motivation and decreased student academic achievement. Therefore, active parental involvement needs to be continuously improved through effective communication and good collaboration with the school so that children's academic and non-academic development can be achieved optimally. This research is expected to be a reference for parents and educators in improving the quality of children's learning in elementary schools.